Does In-Store Marketing Work? Effects of the Number and Position of Shelf Facings on Brand Attention and Evaluation at the Point of Purchase - Chandon, Pierre; Hutchinson, J. Wesley; Bradlow, Eric T.; Young, Scott H. (Journal of Marketing, 2009)
Recent trends in marketing have demonstrated an increased focus on in-store expenditures with the hope of “grabbing consumers” at the point of purchase, but does this make sense? To help answer this question, the authors examine the interplay between in-store and out-of-store factors on consumer attention to and evaluation of brands displayed on supermarket shelves. Using an eye-tracking experiment, they find that the number of facings has a strong impact on evaluation that is entirely mediated by its effect on visual attention and works particularly well for frequent users of the brand, for low-market-share brands, and for young and highly educated consumers who are willing to trade off brand and price. They also find that gaining in-store attention is not always sufficient to drive sales. For example, top- and middle-shelf positions gain more attention than low-shelf positions; however, only top-shelf positions carry through to brand evaluation. The results underscore the importance of combining eye-tracking and purchase data to obtain a full picture of the effects of in-store and out-of-store marketing at the point of purchase.